A specific and efficient photoreaction between E. coli RNA polymerase and T+1 in the lacUV5 or deoP1 promoter. - Jeppesen, C (1988)
Upon irradiation of the RNA polymerase-lacUV5 or deoP1 promoter complex with short wavelength ultraviolet light (lambda less than or equal to 300 nm) the polymerase is covalently crosslinked at an efficiency of greater than 10% to the first transcribed base of the template DNA strand when this is a thymine. The temperature dependence of this RNA polymerase-T+1 photoreaction strongly indicates a relation to the formation of the open complex. It is suggested that open complex formation is preceded or accompanied by a specific contact between the RNA polymerase and the first transcribed base of the DNA template.